The Effect of Benson’s Relaxation Therapy on Stress Levels Among Medical Students Diponegoro University Who Were Working on a Thesis - Erlangga Hadi Kesuma; Yosef Purwoko; Muflihatul Muniroh; Natalia Dewi Wardani (Jurnal Kedokteran Diponegoro, 2024)
Background: The prevalence of stress in final-year students who were working on a thesis was still quite high. Unmanaged stress could bring a negative impact on the students themselves. Benson’s relaxation therapy was a relaxation that combined deep breathing techniques with faith factor and had been known to reduce stress levels. This relaxation was easy to do, safe, and didn’t require a lot of time and money. Research related to the effect of Benson's relaxation on student stress levels was also still limited. Objective: To analyze the effect of Benson’s relaxation on stress levels in students of the Faculty of Medicine Diponegoro University who were working on a thesis. Methods: Quasi-experimental study with pre-test and post-test design. This research involved 64 final-year medical students and divided into two groups. A consecutive sampling technique was performed. The experimental group (n=32) were instructed to do Benson’s relaxation therapy for 14 days, each day 2 session for 10 minutes, and the control group were instructed to not do any exercise and other relaxation. The stress levels was measured with the Perceived Stress Scale (PSS). Data’s significance was analyzed with paired sample T-test and independent sample T-test. Results: A significant decrease (p<0,001) in stress level before and after Benson relaxation, from 16,34 ± 6,91 to 11,31 ± 4,79. The post-test stress level of the experimental group (11,31 ± 4,79) was significantly (p=0,001) lower than the control group (16,09 ± 5,79). Meanwhile, there were no significant differences on the pre-test stress level between two groups (p=0,781). Conclusion: Benson’s relaxation reduced stress levels in students of the Faculty of Medicine Diponegoro University who were working on a thesis.